Kazimierza Laskowskiego powieść o łódzkim lokaucie - Sobieraj, Tomasz (My University, 2011)
The article deals with the interpretation of the novel Lockout by Kazimierz Laskowski (1861-1913), the second-rate polish writer of the Young Poland epoch. The plot of Lockout is based on dramatic events of 1905 revolution in Lodz, one of the biggest cities of Congress Poland. Lodz, called the Polish Manchester, was then the centre of textile industry. Laskowski’s Lockout is justly regarded as the novel of purpose. The basic aim of the author was to criticize an action taken by Lodz’s employers in 1907. The novel gives a tendentious view of the Jewish and German bourgeoisie exploiting Polish ordinary workers.
Keywords: Congress Poland; 1905 revolution; Novel of purpose; Works by Kazimierz Laskowski